Pengaruh Product Quality dan Service Quality terhadap Brand Switching Melalui Customer Value (Studi pada Mantan Pelanggan Indihome di Kota Semarang) - Hapsari Wahyu Widyaningrum; Naili Farida; Apriatni Endang Prihatini (Jurnal Ilmu Administrasi Bisnis, 2022)
This study aims to determine the effect of product quality and service quality on brand switching through customer value” (study of former IndiHome customers in Semarang). This type of research is explanatory research. The sampling method in this research is non-probability sampling by purposive sampling. The data collection process uses Google forms with 100 respondents from former IndiHome customers in Semarang City as the research sample. The analysis used is regression analysis and path analysis. The results of the research show that product quality has an effect on customer value, service quality has an effect on customer value, product quality has a negative effect on brand switching, service quality has no effect on brand switching, and customer value has no effect on brand switching. The results of the path analysis show that there is an indirect effect between product quality on brand switching through customer value, so that customer value partially mediates between product quality and brand switching. in addition, there is a direct influence between service quality on brand switching through customer value, so that customer value cannot partially mediate between service quality and brand switching. Suggestions that can be given to IndiHome include updating core products and innovations in features, increasing customer awareness regarding the My IndiHome application and conducting training for officers, providing discounts or promos at certain times and actively contacting customers regularly to ensure whether there are complaints. and what problems the customer is experiencing.